2016
DOI: 10.1136/ejhpharm-2016-000957
|View full text |Cite
|
Sign up to set email alerts
|

Mandatory dexamethasone strictly monitored by pharmacists reduces the severity of pemetrexed-induced skin rash

Abstract: ObjectiveThe present study aimed to retrospectively examine the effectiveness of mandatory dexamethasone (m-DEX) strictly monitored by pharmacists collaborating with medical physicians and nurses for reducing pemetrexed (PEM)-induced skin rash in patients with non-squamous non-small-cell lung cancer (ns-NSCLC).MethodsWe compared the rash grades during the first cycle of PEM-containing regimens between patients who received m-DEX after February 2012 and those who received dexamethasone (DEX) at their physician'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Piérard et al suggested that a high Ki67 index could point towards cell cycle blockade versus calprotectin (MAC 387) immunopositivity of keratinocytes as a soft indictor of immunological perturbation 4. Usui et al in their study concluded that mandatory dexamethasone as premedication before pemetrexed-based therapy reduced the frequency of grade ≥2 skin rash by at least 10% 5. In past, many anti-cancer drugs are reported to be associated with dermatological adverse effects (6,7) .…”
Section: Descriptionmentioning
confidence: 99%
“…Piérard et al suggested that a high Ki67 index could point towards cell cycle blockade versus calprotectin (MAC 387) immunopositivity of keratinocytes as a soft indictor of immunological perturbation 4. Usui et al in their study concluded that mandatory dexamethasone as premedication before pemetrexed-based therapy reduced the frequency of grade ≥2 skin rash by at least 10% 5. In past, many anti-cancer drugs are reported to be associated with dermatological adverse effects (6,7) .…”
Section: Descriptionmentioning
confidence: 99%